2012
DOI: 10.1080/13504622.2011.576316
|View full text |Cite
|
Sign up to set email alerts
|

Writing to learn ecology: a study of three populations of college students

Abstract: Being an ecologically literate citizen involves making decisions that are based on ecological knowledge and accepting responsibility for personal actions. Using writing-to-learn activities in college science courses, we asked students to consider personal dilemmas that they or others might have in response to how human choices can impact coastal dead zones around the world. We explored how undergraduate students (42 biology and 47 elementary education majors at a 4-year college and eight Native studies majors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 55 publications
2
21
0
1
Order By: Relevance
“…The results concerning the academic success of the students reveal out a parallelism with the studies conducted by making use of the WTL activity (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Considering the values obtained at the end of the research, it was found that; the students who were taught the SPT through the letter writing activity, which is one of the WTL activities, became more successful than the students who were taught through the traditional teaching method.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The results concerning the academic success of the students reveal out a parallelism with the studies conducted by making use of the WTL activity (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Considering the values obtained at the end of the research, it was found that; the students who were taught the SPT through the letter writing activity, which is one of the WTL activities, became more successful than the students who were taught through the traditional teaching method.…”
Section: Resultssupporting
confidence: 66%
“…In simple words, these activities can be defined as designs where the learners explain how they perceive the scientific expressions and concepts and how they re-create those themselves, instead of a way of communication with the teacher [7]. They are based on concepts and learning [8]. The students can use WTL activities to express the subject they have learned with their own opinions through writing [9].…”
Section: Introductionmentioning
confidence: 99%
“…Lessons on SSIs allow classroom educators to examine the reasoning strategies that students employ as they make sense of the social and moral consequences of decisions related to the issue (Sadler, ; Sadler & Zeidler, ; Zeidler & Schafer, ). In our previous studies, we found that there were distinct differences between the types of claims and evidence that students from different majors and institutions (Public University and Tribal Community College) used (Balgopal et al, ). Biology majors made claims that were more anthropocentric than the education majors, who were more likely to be environmentally centric.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We did not expect the participating students to replace or express a specific epistemology. Rather, our goal was to allow them to ground arguments in their own cultural epistemologies (Bang & Medin, ) by designing writing prompts that let students (i) use their own voice (Wallace, ); (ii) explicitly draw on personal funds of knowledge (Moje et al, ); (iii) consider a locally relevant SSI of which many of them were already aware (e.g., Kolstø, ); and (iv) recognize that we were not looking for “right or wrong answers” (Balgopal, Wallace, & Dahlberg, ). We analyzed the types of claims students made, the types of evidence used to support claims, and how arguments were framed.…”
mentioning
confidence: 99%
“…The students can evaluate any changes or developments in their ideas about the subjects they learn at schools by writing and at the same time they learn what the scientifiic processes are (Balgopal, Wallace & Dahlberg, 2012). The scientific process skills include some skills such as observation, guessing, measuring and classification, recording the data, forming hypotheses and determining the variables (MNE, 2013).…”
Section: Introductionmentioning
confidence: 99%